An Agile-Scrum Approach to Enhancing Urban Transit through a Mobile-Based Motorcycle Parking System with OCR Integration - Abadi Suryo Setiyo; Ana Kurniawati (Bulletin of Computer Science Research, 2026)
This study discusses the development of a mobile-based motorcycle storage application using the Agile Scrum method in the 359 Parking service in the Pondok Cina Station area. The application was developed to help manage vehicle storage digitally through storage location search features, vehicle reservations, and vehicle identification using Optical Character Recognition (OCR) technology. The system is built using Flutter and Firebase with the implementation of Google ML Kit OCR to help with the automatic scanning of vehicle license plates. Data collection was carried out through literature studies, interviews, and numerical scale forms on customers and motorcycle storage managers. System testing is carried out using the Black Box Testing method on the main features of the application. The test results show that the login, reservation, location search, and vehicle license plate scanning features can run according to the functional needs of the system. The implementation of OCR also helps reduce the manual recording process of vehicles, especially in adequate lighting conditions. In addition, user evaluation results show that the app helps simplify the process of finding a storage location and managing a vehicle. This study shows that the application of mobile technology, location services, and OCR can support the digitization of motorcycle storage services to be more effective and integrated.